The microbial metabolite imidazole propionate dysregulates bone homeostasis by inhibiting AMP-activated protein kinase (AMPK) signaling - Suk-Gyun Park; Jung-Woo Kim; Ju Han Song; Seung-Hee Kwon; Sin-Hye Oh; Xianyu Piao; Zhao Wang; Je-Hwang Ryu; Nacksung Kim; Ok-Su Kim; Jeong-Tae Koh (Communications Biology)
Abstract Microbial metabolites provide numerous benefits to the human body but can also contribute to diseases such as obesity, diabetes, cancer, and bone disorders. However, the role of imidazole propionate (ImP), a histidine-derived metabolite produced by the intestinal microbiome, in bone metabolism and the development of osteoporosis is still poorly understood. In this study, we investigated the role of ImP and its underlying mechanisms in regulating bone homeostasis. When ImP was administered to 8-week-old mice for 4 weeks, bone loss was observed, along with a decrease in alkaline phosphatase-positive osteoblast cells. Additionally, bone marrow stromal cells (BMSCs) isolated from ImP-treated mice exhibited reduced osteogenic potential. In BMSCs from control mice, ImP treatment inhibited BMP2-induced osteoblast differentiation while promoting adipocyte differentiation. However, ImP had no effect on RANKL-induced osteoclast differentiation or activity in bone marrow macrophages. Mechanistically, ImP treatment increased p38γ phosphorylation and decreased AMPK (T172) phosphorylation in BMSCs. Suppression of p38γ expression using si-p38γ reversed the inhibitory effects of ImP on osteoblast differentiation, with a concurrent increase in AMPK (T172) phosphorylation. Conversely, ImP stimulated adipocyte differentiation by decreasing AMPK (T172) phosphorylation. Treatment with the AMPK agonist metformin significantly reversed the inhibitory effects of ImP on osteoblast differentiation and the promotion of adipocyte differentiation, along with enhanced AMPK (T172) phosphorylation. These findings suggest that the microbial metabolite ImP may disrupt bone homeostasis by stimulating p38γ phosphorylation and inhibiting the AMPK pathway, presenting a potential therapeutic target for managing metabolic bone diseases.